Influence of calcination time and heating rate on the phase-chemical structure of Pd-doped SiO2 organic-inorganic membrane materials in air. (11th June 2018) - Yang, Jing; Fan, Wangqing; Li, Hongji; Mu, Ruihua; Hou, Haiyun
ABSTRACT: Pd-doped SiO2 organic-inorganic hybrid materials were synthesized using sol-gel technique. The Pd-doped SiO2 samples were calcined at the temperature 350°C for several different time in air atmosphere with two different heating rates. Influence of calcination time and heating rate on the phase-chemical structure of Pd-doped SiO2 membrane materials was discussed by XRD, XPS, FTIR and TG-DTG analysis. The results indicate that the two factors have great influence on the crystal structure of Pd element and minor influence on the chemical structure. A longer calcination time and a slower heating rate can facilitate the oxidation of Pd 0 to PdO, and should be conducive to the decomposition of Si-CH3 groups and the dehydration condensation of Si-OH groups. In order to prevent metallic Pd 0 in Pd-doped SiO2 organic-inorganic membrane materials from being oxidized in air, the calcination time and heating rate should be chosen carefully.